Sheikh Muhammad al-Khal's efforts in reviving the biographies of Kurdish scholars, with al-Bitushi, al-Nudhi, and al-Zahawi as examples. - Aziz, Dr. Hamid Muhammad Amin (Sulaimani Journal for Humanities, 2023)
This research examines the efforts of Sheikh Muhammad al-Khal in compiling biographies of three Kurdish scholars: Allama Mulla Abdullah al-Bitushi, Sheikh Ma'ruf al-Nawdahi al-Barzanji, and Mufti Muhammad Faydi al-Zahawi. Sheikh al-Khal dedicated a book to each of these three luminaries. The researcher attempts to highlight Sheikh al-Khal's motivations for writing these books and the sources he relied upon. The researcher also presents the topics and issues covered in these books, including the biographies of these three figures and other scholarly matters that Sheikh al-Khal appended to his three works. The researcher records observations and comments on these books. This research demonstrates that Sheikh al-Khal demonstrated considerable creativity in these works, recording important information and critically editing numerous poems, letters, and other writings of these scholars.
Keywords: Translations; AlKhal; AlBitoshi; AlNoudhi; AlZahawi; History of Kurdish Scholars